AZURE CLOUD NATIVE ARCHITECTURE MAPBOOK explore the microsoft cloud's infrastructure,... application, data, and security architecture. - Eyskens, Stephane (PACKT PUBLISHING LIMITED, 2021)
Improve your Azure architecture practice and set out on a cloud and cloud-native journey with this Azure cloud native architecture guide Key Features Discover the key drivers of successful Azure architecture Implement architecture maps as a compass to tackle any challenge Understand architecture maps in detail with the help of practical use cases Book DescriptionAzure offers a wide range of services that enable a million ways to architect your solutions. Complete with original maps and expert analysis, this book will help you to explore Azure and choose the best solutions for your unique requirements. Starting with the key aspects of architecture, this book shows you how to map different architectural perspectives and covers a variety of use cases for each architectural discipline. You'll get acquainted with the basic cloud vocabulary and learn which strategic aspects to consider for a successful cloud journey. As you advance through the chapters, you'll understand technical considerations from the perspective of a solutions architect. You'll then explore infrastructure aspects, such as network, disaster recovery, and high availability, and leverage Infrastructure as Code (IaC) through ARM templates, Bicep, and Terraform. The book also guides you through cloud design patterns, distributed architecture, and ecosystem solutions, such as Dapr, from an application architect's perspective. You'll work with both traditional (ETL and OLAP) and modern data practices (big data and advanced analytics) in the cloud and finally get to grips with cloud native security. By the end of this book, you'll have picked up best practices and more rounded knowledge of the different architectural perspectives. What you will learn Gain overarching architectural knowledge of the Microsoft Azure cloud platform Explore the possibilities of building a full Azure solution by considering different architectural perspectives Implement best practices for architecting and deploying Azure infrastructure Review different patterns for building a distributed application with ecosystem frameworks and solutions Get to grips with cloud-native concepts using containerized workloads Work with AKS (Azure Kubernetes Service) and use it with service mesh technologies to design a microservices hosting platform Who this book is for This book is for aspiring Azure Architects or anyone who specializes in security, infrastructure, data, and application architecture. If you are a developer or infrastructure engineer looking to enhance your Azure knowledge, you'll find this book useful.